2013
DOI: 10.5251/abjna.2013.4.4.422.429
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the determinants of poverty among artisanal fishing households in Edu and Moro local government areas of Kwara State, Nigeria

Abstract: The study examined poverty and estimate its determinants among artisanal fishery households in Edu and Moro Local Government Areas of Kwara State. A multi stage random sampling technique was used to select 160 fishermen for the study. Primary data were obtained with the aid of well structured questionnaire and interview schedule. Descriptive statistics and tobit regression model were employed in the analysis of the data. 69.4% of pooled fishermen did not have formal schooling and about 91% were males. Using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
2
8
0
Order By: Relevance
“…Education is a vital route to improved efficiency and increased yield which in turn reduces poverty. The result was synonymous with findings of Schubert (1994), FOS (1999, Etim and Patrick (2010) and Oladimeji et al (2013) who observed that people with lower levels of education were more prone to poverty.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Education is a vital route to improved efficiency and increased yield which in turn reduces poverty. The result was synonymous with findings of Schubert (1994), FOS (1999, Etim and Patrick (2010) and Oladimeji et al (2013) who observed that people with lower levels of education were more prone to poverty.…”
Section: Discussionsupporting
confidence: 78%
“…Also, in the region, male-headed farm households are usually involved in other off-farm activities which provide additional income and hence enhancement of household welfare. Federal Office Statistics (1999), Osinubi (2003), Etim (2007), Etim and Patrick (2010), Oladimeji et al (2013) found that the incidence of poverty in female-headed households was higher than in male-headed households across Nigeria. This result is vital as it reveals the importance of integrating/mainstreaming gender in future poverty related studies among smallholder farmers in the area.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations